Harmonisasi Tata Kelola: Mengurai Benang Kusut Kebijakan Pendidikan Nasional dan Daerah di Era Otonomi - Riza Ummaroch; Dedi Kurniadi; Agus Tinus (J-SES : Journal of Science, Education and Studies, 2026)
This research aims to map and analyze the problems of education policy synchronization between the central and regional governments within the framework of regional autonomy in Indonesia. Regulatory misalignment is often a major obstacle to the equitable distribution of national education quality. The research method used is descriptive qualitative with a document study and public policy analysis approach. The research results show that the "tangled thread" phenomenon of policy is triggered by overlapping administrative authorities, differing budget priorities, and weak cross-sectoral communication. These findings emphasize that governance harmonization requires standardization of operational procedures that are flexible yet nationally controlled. Education information system integration and strengthening vertical-horizontal coordination are crucial solutions to ensure central policies can be implemented effectively at the regional level without ignoring local wisdom contexts. Educational bureaucracy reform must be directed at creating a responsive and collaborative policy ecosystem to achieve the targets of superior human resource development.